Effect of pre-treatment of strength training and raloxifene in periestropause on bone healing - Peres-Ueno, Melise Jacon [UNESP] (2020)
Background: There is evidence that strength training (ST) and raloxifene (Ral) treatment during periestropause promotes better bone quality. We wanted to determine whether the skeletal benefits of ST or Ral treatment, performed during periestropause, would persist after fracture. Therefore, the present study aimed to analyze the influence of pre-treatment with ST and administration of Ral during periestropause on bone healing after total unilateral osteotomy. Methods: Senescent female Wistar rats between 18 and 21 months of age, performed ST on a ladder three times per week, were administered Ral by gavage (2.3 mg/kg/day), or an association of both. After 120 days, the treatments were interrupted, and a total osteotomy was performed on the left tibia in all animals. They were euthanized 1 and 8 weeks post-osteotomy. Results: The administration of Ral during periestropause worsened the biochemical and oxidative profile, decreased gene expression of markers related to bone resorption and remodeling, which negatively affected the physicochemical properties; this lead to changes in the bone callus microarchitecture and mass, as well as a decrease in callus resistance to torsional deformation, resulting in lower tissue quality during bone healing. In contrast, ST performed prior to the osteotomy resulted in better bone healing, improvement of the biochemical and oxidative profile, alteration of the genetic profile in favor of bone formation and resorption, as well as the physic-ochemical properties of the callus. These changes led to better microarchitecture and bone mass and increased callus resistance to torsional deformation, confirming its beneficial effect on the quality of bone tissue, providing acceleration of bone consolidation. The combination of therapies at this exercise intensity and drug dosage showed a negative interaction, where the negative effect of Ral overcame the positive effect of ST, leading to decreased tissue quality in the bone healing process. Conclusions: This study indicates that in addition to excellent non-pharmacological therapy and action in the prevention of osteoporosis, ST performed during the aging period may increase bone quality at the onset of healing and provide improved bone consolidation. Furthermore, the anti-osteoclastogenic effect of Ral shown in this model delayed the bone repair process, resulting in considerable clinical concern.